THE RELATIONSHIP BETWEEN CONCEPTUAL UNDERSTANDING AND PROBLEM-SOLVING ABILITIES IN FORCE AND MOTION AMONG PHYSICS UNDERGRADUATES IN MALAYSIA - Krisantini Vinayagan; Fatin Aliah Phang; Faizani (Joint Prosiding IPS dan Seminar Nasional Fisika, 2026)
This study was conducted to better understand how students’ conceptual knowledge influences their ability to solve physics problems, particularly in the topic of force and motion. This study investigates the relationship between conceptual understanding and problem-solving ability in the topic of force and motion among undergraduate physics students at a university in Malaysia. The research aimed to determine the relationship between conceptual understanding, assessed using the Force Concept Inventory (FCI), and problem-solving ability, assessed using the Scholastic Assessment Test (SAT) Physics Practice Test focusing on Newton’s Laws. A total of 60 respondents who had completed the Mechanics course participated in this study. Descriptive analysis using frequency distribution was conducted to evaluate the levels of both conceptual understanding and problem-solving ability. The results showed that 41.67% of students demonstrated Partial Understanding, 38.33% had Limited Understanding, 13.33% showed Not Understanding, and only 6.67% achieved Sound Understanding. For problem-solving ability, 50.00% of the students were at the Intermediate level, 26.67% were classified as Expert, and 23.33% as Novice. To determine the relationship between the two variables, Pearson Correlation analysis revealed a moderate negative correlation (r = –0.488, p = 0.049), indicating a statistically significant inverse relationship between students’ conceptual understanding and their problem-solving ability in force and motion. The findings highlight the need for instructional approaches that address conceptual understanding and problem-solving as distinct yet interconnected skills in physics education.